PROFILE OF FAMILY MEMBERS AND USERS OF A PSYCHIATRIC SERVICE OF CAPE VERDE, AFRICA - Ana Suzete Baessa Moniz; Mara Regina Santos da Silva; Edison Luiz Devos Barlem; Luciano Garcia Lourenção (Universidade Federal do Paraná, 2019)
Objective: to characterize the profile of users of the Extensão Trindade Psychiatric Hospital in Cape Verde, Africa, and to characterize the profile of the family members of these users. Method: a descriptive study was conducted in 2016 with 100 people who were hospitalized in the psychiatry service, between 2010 and 2015, and 30 randomly selected family members. Data collected in the psychiatric hospital (medical records) and in the home (interview) were analyzed in a descriptive way.Results: 67.0% of the users were male, 82.0% single and 87.0% had one to ten hospital readmissions; 90.0% of the family members were female, 43.3% mothers and 73.3% did not know the mental disorder of the family member.Conclusion: the study allowed the identification of the profile of users of the psychiatry service in Cape Verde, Santiago Island and that of their family members, contributing to the strategy of nursing care for families and people with mental disorder after hospital discharge